(untitled) (Indonesian Economic Justice Review, 2025)
This paper explores the intersection of economic justice and indigenous land rights in Indonesia, focusing on the state’s role in balancing development with the protection of indigenous communities. Indonesia’s rapid economic growth, fueled by natural resource extraction, has led to widespread land dispossession, particularly affecting indigenous communities who depend on these lands for their livelihoods. The study examines key policies and legal frameworks that govern land use and indigenous rights, such as the 2013 Constitutional Court ruling on indigenous land recognition. Despite legal advancements, land-grabbing practices, particularly by palm oil and mining companies, continue to undermine indigenous land claims. The paper analyzes the ways in which Indonesia’s economic policies prioritize national development over the rights of indigenous communities, resulting in social displacement and environmental degradation. It also critiques the role of the state in failing to enforce laws that protect indigenous land rights, highlighting the tension between economic development and social justice. Drawing on case studies of indigenous communities in Kalimantan and Papua, the paper evaluates the effectiveness of legal frameworks in securing land rights and ensuring that development projects do not disproportionately disadvantage indigenous peoples. The paper concludes with policy recommendations for improving the legal protections for indigenous land rights and ensuring more equitable economic development.